2020
DOI: 10.1021/acssuschemeng.9b06329
|View full text |Cite
|
Sign up to set email alerts
|

Spindle-Like MOF Derived TiO2@NC–NCNTs Composite with Modulating Defect Site and Graphitization Nanoconfined Pt NPs as Superior Bifunctional Fuel Cell Electrocatalysts

Abstract: The modulating degree of defect and graphitization carbon coupled metal oxide composite is extremely important because these materials have been applied in various fatal fields, especially in energy storage/conversion and catalysis. Herein, we reported the in situ formation of long defect-rich nitrogen-doped carbon nanotubes (NCNTs) coupled with a porous TiO 2 @NC composite (TiO 2 @NC−NCNTs) derived from spindletype bimetallic (Ti/Co) MOF microrods. Thanks to the rational composition and unique structure, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The bi-functional mechanism could be summarized as follows (Levy and Boudart, 1973;Wang et al, 2006;Lu et al, 2016 (Wang et al, 2014;Jin et al, 2020). As time goes by, the current decreases slowly.…”
Section: Resultsmentioning
confidence: 99%
“…The bi-functional mechanism could be summarized as follows (Levy and Boudart, 1973;Wang et al, 2006;Lu et al, 2016 (Wang et al, 2014;Jin et al, 2020). As time goes by, the current decreases slowly.…”
Section: Resultsmentioning
confidence: 99%
“…(d) Schematic process used to construct Pt/TiO 2 @NC-NCNTs. Image reprinted with permission from ref . Copyright 2020 American Chemical Society.…”
Section: Synthesis and Structure Tuning Strategies Of Mofsmentioning
confidence: 99%
“…The defect and graphitization degree may be effectively optimized by tuning the Ti and Co ratio in the MOF precursor, which is a fascinating phenomenon. Carbon samples, such as NCNTs and N-doped carbon, demonstrate high surface area sites for Pt deposition while also speeding up electron transport during the electrochemical process …”
Section: Synthesis and Structure Tuning Strategies Of Mofsmentioning
confidence: 99%
“…The more effective method to endow the catalyst with high anti-CO poisoning ability is introduction of the oxygen donors such as transition metal oxide, metal hydroxides, and metal hydroxyl carbonates . According to the Langmuir–Hinshelwood (L–H) pathway, it is supposed that the metal oxides (MO) such as SnO 2 , CeO 2 , and TiO 2 with abundant hydroxyl groups or dissociated OH – are beneficial for the desorption of CO to release the active sites. Furthermore, the strong metal–support interaction (SMSI) between Pd and MO downshifts the d band states of Pd, mitigating the mutual interaction between Pd and CO ads . Recently, several works have suggested that noble metal–semiconductor catalysts present enhanced MOR activity and CO tolerance through the fast photoactive process in the photo-electrocatalyst–electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%